2017
DOI: 10.1080/24749508.2017.1301062
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the influence of tunnel portal section construction on slope stability

Abstract: High-speed railway tunnel entrance as the basis, combined with the actual engineering geological conditions, the establishment of a dynamic construction of three-dimensional model of tunnel entrance. With the analysis of soil excavated hole portion of the hole and the hole body during deformation movement of surface soil slope. The main conclusions are: (1) on the stepped portion of the hole excavation on the scope of the maximum slope excavation slope deformation rate in step fastest, over time, the deformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…For example, Zhou et al (1998) showed that there are temporal differences in the response of soil moisture at different depths to precipitation. For instance, the soil moisture at soil depth of 30 cm and 60 cm reaches the maximum value at the first time lag interval after a precipitation event, while the soil moisture at soil depth of 90 cm and 110 cm reaches the maximum value at 4 and 8 time lag intervals, respectively, where one time lag interval is 5 days (Wang et al, 2017). The main reason for the differences in the study results is due to different study areas, vegetation, soil texture, meteorological elements, and soil moisture monitoring time intervals (Jacques et al, 2001;Wendroth et al,1999).…”
Section: Cross-correlation Analysis Between Soil Moisture and Precipimentioning
confidence: 99%
“…For example, Zhou et al (1998) showed that there are temporal differences in the response of soil moisture at different depths to precipitation. For instance, the soil moisture at soil depth of 30 cm and 60 cm reaches the maximum value at the first time lag interval after a precipitation event, while the soil moisture at soil depth of 90 cm and 110 cm reaches the maximum value at 4 and 8 time lag intervals, respectively, where one time lag interval is 5 days (Wang et al, 2017). The main reason for the differences in the study results is due to different study areas, vegetation, soil texture, meteorological elements, and soil moisture monitoring time intervals (Jacques et al, 2001;Wendroth et al,1999).…”
Section: Cross-correlation Analysis Between Soil Moisture and Precipimentioning
confidence: 99%
“…However, in tunneling, there is no specific procedure to assess the behavior of the rock mass during digging with respect to the failure mechanism previously defined in the design process [16][17][18]. Hence, the stability of portal slopes should not be considered separately from tunneling [19][20][21], because the collapse that may occur during the excavation of the portal will completely stop the tunnel digging [22][23][24][25][26][27]. Thus, practical limitations greatly affect the ability to assess the stability of rock sections and slopes in real time, so we use analytical methods such as kinematics, LE, FE or discrete element modeling [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Bennion et al (1994) have also provided a detailed discussion of the mechanisms of aqueous phase trapping. Penny et al (1983) pointed out that the capillary pressure, wettability and relative permeability are controlling the load water recovery following hydraulic fracturing treatments (Wang 2017). Since the fractal dimension has certain links with both of the capillary pressure and relative permeability, it can be used to evaluate the potential water blocking in tight gas reservoir.…”
Section: Batuan DI Takungan Kedap Gas Lebih Heterogen Daripada Takungmentioning
confidence: 99%